Исследование возможности синтеза гидроксилапатита биомедицинского назначения из растворов и гидротермальным методом - Кривилева, Светлана Павловна (НТУ "ХПИ", 2015)
В статье рассмотрены различные методы получения синтетического гидроксилапатита биомедицинского назначения. Выполнена оценка возможностей синтеза кристаллического Сa₁₀(PO₄)₆(OH)₂ высокой чистоты «мокрым» способом из растворов Сa(OH)₂ и Н₃РО₄, и гидротермальным методом из CaСО₃, Ca(OH)₂ и предварительно синтезированного Сa₃(PO₄)₂. Определены оптимальные концентрации растворов, сроки и параметры смешения, режимы термообработки, рН среды, время выдержки в исходных растворах, а также соотношение исходных компонентов и режимы автоклавирования. Определено, что для получения гидроксилапатита стехиометрического состава наиболее перспективным является растворный метод.

The article describes on various methods for producing a synthetic hydroxyapatite. Hydroxyapatite of biomedical use produces by hydrolysis, anhydrous calcium phosphate, pyrolysis (decomposition solutions of base components in the hot zone of the reactor with their subsequent interaction) and deposition from solutions followed by freeze-drying and sublimation. The evaluation of the feasibility of synthesis of the crystalline Сa₁₀(PO₄)₆(OH)₂ of high purity is made of solutions and a hydrothermal method. It is established that the stoichiometric ratio of the components and the geometrical dimensions of the produced crystals varies the regulation of phosphate ions state in the initial solution and the aging time. The parameters of the transition of the materials obtained in the crystalline state (due to residual absorption of calcium from the initial solution by mutual ordering of the primary microelements, and combining into crystals). The optimal concentration and time of components mixing, the environment of pH and parameters of endurance in the initial solution for receiving materials of the set composition and structure are defined. Schemes of formation, the modes of crushing and heat treatment providing ensure synthesis Сa₁₀(PO₄)₆(OH)₂ of high purity with autoclave method are developed. It is defined that receiving a hydroxyapatite in the "wet" way which less energy-intensive is more perspective.
Study the possibility of synthesis hydroxyapatite for biomedical applications from the solution and the hydrothermal method
Keywords: фосфат трехкальциевый; гидратация; биокерамика; анализ рентгенофазовый; фазообразование; tricalcium phosphate; hydration; bioceramic materials; X-ray phase analysis; phase formation